Epidemiology investigation of typhoid incidence in senior high school X in Magelang District - Ahmad, Nasir; Isworo, Adi; Indriani, Citra (Universitas Gadjah Mada, 2021)
Purpose: This study aimed to determine the magnitude and cause of the outbreak, describe the outbreak based on person, place, and time, and implement control measures. Methods: This study uses descriptive epidemiology and looks for active cases to find additional cases. Cases included students with fever with or without further symptoms: dizziness, nausea, vomiting, headache, stomachache, diarrhea, and chills from September 28 to November 28. Data collection was carried out through interviews using a standard questionnaire. We took clean water, drinking water, and blood samples. The water sample was sent to the Environmental Health Laboratory, and the blood sample to a private laboratory in Magelang for an IgM anti-Salmonella typhi test. Results: The number of cases was 150 students. The highest attack rates were among women, 72/359 (20.1%), and first-year students, 139/381 (36.48%). The onset of the disease starts from 28 September to 26 October 2016. There are outbound activities on the river on 26 September, attended by all first-year and second- and third-year students, as part of the activity committee. This activity is followed by eating together before and after washing hands with soap. All cases attended outbound activities. IgM was positive in 51 students, and water samples were negative for Salmonella typhi. Conclusion: There was an outbreak of typhoid fever with 150 cases in schools from 28 September to 28 November 2016. The outbreak was caused by the lack of hand-washing with soap when eating. We provide medical and health education to students about typhoid fever. The recommendation is to make school rules about the behavior of washing hands with soap, and if you take a bath in the river, before eating, it is necessary to wash your body and hands with soap.